Oscillatory flow driven microdroplet breakup dynamics and microparticle formation in LMPA-water two phase flow system - Yanhong Guo; Yong Liu; Tuo Hou; Xinyu Zhang; Jiayun Gao; Jun He; Chengbo Wang; Jing Wang; Qingsen Zhao; Yue Chan; Yong Ren (Engineering Applications of Computational Fluid Mechanics)
This study presents a mathematical modeling and numerical investigation of oscillatory flow induced microdroplet breakup in low melting point alloy (LMPA)-in-water two-phase flow system in a microchannel. The effects of perturbation flow Weber number, and oscillating frequencies on the droplet breakup dynamics have been elucidated. Lowering the wall temperature will accelerate the solidification process of LMPA droplets, giving rise to the rapid formation of ultra-small particles with size down to 1 micron in less than 3 ms. The versatile approach combines oscillatory flow dominated droplet breakup process and phase change process, leading to the formation of LMPA microparticles with monodispersed size distribution and well-tailored properties by using a straight microchannel, which obviates the need for sophisticated design and complex fabrication process of microdevices. This work will provide a strategy to manipulating LMPA droplet size and structure for the massive production of ultra-small LMPA microparticles via a facile control over the flow conditions in the two-phase flow in a microfluidic system. It will open up for a diversity of applications of LMPA microparticles in various fields such as energy storage and thermal management.